Repayment patterns, financial discipline and consumer profiling: an empirical investigation among credit card users in Malaysia - Hussin, Siti Rahayu; Kassim, Salina (IDOSI Publications, 2013)
This study attempts to investigate the extent of financial discipline being observed by the credit card users in Malaysia and subsequently relate the financial discipline levels to the profile of the credit card users. To measure financial discipline, the study focuses on repayment preference of the card users, as to whether they would pay in the full amount of the outstanding balance, pay according to ability, or pay the minimum required amount. Descriptive analysis is used to describe the profile of the credit card users, while the relationship between the repayment preferences and credit card users’ profile is assessed empirically using Pearson correlation analysis and further substantiated by the chi-square analysis. The results of this study provide information on the segments of the credit card users that are susceptible to financial difficulties, which are of particular interests to the policymakers amid the increasing concerns of consumer indebtedness in this country.